Renal Transplant Outcome in Children with an Augmented Bladder - Pereira, Pedro L.; Rodriguez, Ruben O.; Camblor, Carlota F.; Urrutia, María José M.; Romera, Roberto L.; Roman, Laura E.; Monereo, Enrique J. (Frontiers in Pediatrics, 2013)
Objective: Studies evaluating renal transplant (RT) outcome in children who underwent an augmentation cystoplasty (AC) are contradictory and the current knowledge is based on studies with a limited number of patients. The aim of this study is to compare RT outcome between children who underwent AC and those without augmentation. Patients and methods: A total of 20p who underwent an AC prior to the RT (12 with ureter and 8 with intestine) were enrolled in the study and were compared to a control group of 24p without AC, transplanted in the same time period (1991–2011). Data including; age at transplant, allograft source, urological complications, urinary tract infections (UTI) incidence, the presence of VUR, and patient and graft survival were compared between the groups. Results: Mean age at RT and mean follow-up were 9.7 vs. 7.9 years and 6.9 vs. 7.9 years in the AC group and control group, respectively (NS). The graft originated in living donors for 60% of AC patients and 41.6% of the control RT patients. The rate of UTI were 0.01 UTI/patient/year and 0.004 UTI/patient/year in the augmented group and controls, respectively (p = 0.0001). In the AC group of 14p with UTIs, 10 (71%) had VUR and 5p out of 8 (62.5%) in the control group had VUR. In the AC group, of the 7p with ≥3 UTIs, 3 (43%) were non-compliant with CIC and the incidence of UTIs was not related with the type of AC or if the patient did CIC through a Mitrofanoff conduit or through the urethra. Graft function at the end of study was 92.9 ± 36.85 ml/min/m2 in the AC group and 88.17 ± 28.2 ml/min/m2 in the control group (NS). Graft survival at 10 years was also similar 88% in the AC group and 84.8% in controls. In the AC group 3p lost their grafts and 5 in the control group with respective mean follow-up of 10.6 ± 4.3 and 7.1 + 4.7 years. Conclusion: There are no significant differences in the RT outcome between children transplanted with AC or without. However, recurrent UTIs are more frequent in the former group and these UTIs are related with non-compliance with CIC or the presence of VUR but, even so, UTIs will not lead to impaired graft function in most of the patients.